Gut Feeling and Digestive Health in Nineteenth-Century Literature, History and Culture (Palgrave Studies in Literature, Science and Medicine, 2018)
This book considers the historical and cultural origins of the gut-brain relationship now evidenced in numerous scientific research fields. Bringing together eleven scholars with wide interdisciplinary expertise, the volume examines literal and metaphorical digestion in different spheres of nineteenth-century life. Digestive health is examined in three sections in relation to science, politics and literature during the period, focusing on Northern America, Europe and Australia. Using diverse methodologies, the essays demonstrate that the long nineteenth century was an important moment in the Western understanding and perception of the gastroenterological system and its relation to the mind in the sense of cognition, mental wellbeing, and the emotions. This collection explores how medical breakthroughs are often historically preceded by intuitive models imagined throughout a range of cultural productions. .